Studying the suspended matter in Antarctic Peninsula coastal waters to understand the local geological and ecological processes - Nasiedkin, Ye.; Olshtynska, O.; Ivanova, G.; Mytrofanova, O. (Ukrainian Antarctic Journal, 2022)
We review comprehensive international studies of the mineral and organic suspended matter in the South Ocean. We suggest an experimental design to monitor these parameters at the Akademik Vernadsky station, where this research will be introduced. Applied aspects of marine suspension’s qualitative and quantitative properties are a subject of active research, given its significance for several physical and biochemical processes such as sedimentation. Therefore, geological, biological, and climatological studies of the Antarctic shelf employ continuous observations of the suspension’s distribution. Work in this area is aimed at investigating the qualitative and quantitative properties of the suspension and analysis of its organic and mineral components, determining the dynamics of the currents and transportation of suspended matter, the nature of sedimentation processes, their seasonality and connection with the direction of currents and movement of sea ice. To determine the possibility of researching the suspended matter in the waters around the Akademik Vernadsky station, we analyze our long-term experience of using sedimentation traps to study the suspended matter flows in the seas and rivers of Ukraine. The developed complex of field equipment can be used to sample the suspended matter in waters adjacent to the Akademik Vernadsky station. The light single-cylinder sedimentation traps were transferred to the team of the Ukrainian Antarctic Expedition 2022 for further use at the Vernadsky station.